Phylogeny and taxonomy of Archilejeunea (Marchantiophyta: Lejeuneaceae) based on molecular markers and morphology. Issue 5 (28th October 2015) - Shi, Xue-Qin; Gradstein, S. Robbert; Zhu, Rui-Liang
Abstract: Archilejeunea, a pantropical liverwort genus of about 22 species, has not been revised worldwide and recent phylogenetic study showed that the genus is not monophyletic. We addressed phylogenetic relationships of Archilejeunea by using nuclear (ITS) and chloroplast ( rbcL, trnL‐F ) DNA regions. Bayesian, likelihood and parsimony phylogenetic analyses of a broad sampling of the group resolved the species in three robust clades, which are morphologically distinct. Based on our molecular phylogenetic results, we split Archilejeunea into two distantly related genera, Archilejeunea s. str. with six species and Dibrachiella stat. nov. with nine species. Both groups have tropical Afro‐American distributions but the range of Archilejeunea is much more restricted than that of Dibrachiella. Archilejeunea is sister to Verdoornianthus from Amazonia and Dibrachiella is member of a clade together with the paleotropical Ptychanthus and Tuzibeanthus, and the pantropical Spruceanthus . Five species previously placed in Archilejeunea ( A. abbreviata, A. amakawana, A. kiushiana, A. olivacea, A. planiuscula ) are resolved in Spruceanthus, which is morphologically very similar to Dibrachiella . Fifteen new combinations and one replacement name are proposed. Ancestral state reconstruction showed that morphological characters traditionally used to define genera of Ptychanthoideae are highly homoplasious. Spruceanthus differs from Dibrachiella in possessing homogeneous oil bodies.